Aldosterone Is Positively Associated With Circulating FGF23 Levels in Chronic Kidney Disease Across Four Species, and May Drive FGF23 Secretion Directly - Radloff, Judith; Pagitz, Maximilian; Andrukhova, Olena; Oberbauer, Rainer; Burgener, Iwan A.; Erben, Reinhold G. (Frontiers in Physiology, 2021)
Background Chronic kidney disease (CKD) is accompanied by increases in circulating fibroblast growth factor 23 (FGF23) and aldosterone levels. Here, we tested the hypothesis that aldosterone may be one of the driving forces behind increased FGF23 secretion in CKD. Methods Using data from a prospective study in humans, a retrospective study in dogs and cats, and an experimental study in 5/6-nephrectomized mice, we analyzed the relationship between circulating FGF23 and serum aldosterone levels in CKD across four species. To assess the effects of acute inhibition of aldosterone signaling on circulating FGF23, we acutely treated mice with established CKD with the mineralocorticoid receptor blocker canrenone (50 mg/kg iv/sc), and measured intact FGF23 before and 24 h as well as 72 h after start of administration of the drug. Results We found a tight positive association between circulating intact FGF23 and serum aldosterone in human, canine, and feline CKD patients, as well as in experimental murine CKD (humans: rS = 0.57, p = 0.0368; dogs: rS = 0.66, p = 0.0019; cats: rS = 0.75, p = 0.0003; mice: rS = 0.49, p = 0.0004). Injection of canrenone in mice with established CKD did not lead to changes in FGF23 levels within 24 h, but reduced FGF23 in all mice at 72 h. Conclusion Aldosterone may drive enhanced FGF23 secretion in CKD, possibly explaining the tight positive association between circulating intact FGF23 and aldosterone in human, canine, and feline CKD patients as well as in experimental CKD models.